Pengaruh Bauran Pemasaran Terhadap Tingkat Penjualan Dalam Perspektif Etika Bisnis Islam Pada Griya Batik Asri Sukoharjo - Sumadi, Sumadi; Sriwalyoto, Sriwalyoto; Haniin, Umi; Rahmawati Husada, Ista Hasri (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the influence of products, prices, places, and promotions in the perspective of Islamic business ethics on the level of sales at Griya Batik Asri Sukoharjo. Sampling was carried out by simple random sampling and for the determination of the number of sample using the slovin formula, which was a total of 86 respondents. The research methods used are quantitative research methods using descriptive statistics, instrument tests, classical assumption tests, and multiple linear analysis. The result of this study partially (t-test) is the effect of products with a t value of 3,886 and a significant value of 0,000 has a positive and significant effect on the level of sales. The effect of price with a t value of 0,048 anf significant 0,962 then has no influence and is not significant on the level of sales. The effect of the place with a t value of 1,522 and a significant 0,132 then has no effect and is not significant on the level of sales. The effect of promotion with a t value of 4,806 and a significant 0,000 has a positive and significant effect on the level of sales.